Evaluation of a 'defouling on demand' strategy for the ultrafiltration of brown water using activatable enzymes - Buchanan, K (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
New approaches to the application of membranes for the production of potable water are constantly being sought after in anticipation of future demands for increasingly rigorous water quality standards and reduced environmental impact. A major limitation, however, is membrane fouling, which manifests itself as a continual reduction in flux over time and thus restricts the practical implementation to restore flux. Mechanical and chemical methods have been implemented to restore flux to ultrafiltration systems, but these either result in a break in the process operation or lead to membrane damage or additional pollution problems. This project was aimed to develop a 'defouling on demand' stategy for cleaning membranes used during brown water ultrafiltration. The process involves the use of activatable peroxidase enzymes, which were immobilised onto flat sheet polysulphone membranes. Following flux decline which reaches a critical level with the build-up of the foulant layer, the immobilised enzyme layer was activated by the addition of a chemical activator solution, in this case hydrogen peroxidase and manganous sulphate. Manganese peroxidase was found to be the most effective enzyme at alleviating fouling by degrading the foulant layer formed on the membrane surface and hence restored flux to the ultrafiltration system. A 93% flux improvement was observed when manganese peroxidase was activated when 800uM manganous sulphate, 100mM hydrogen peroxide were added in the presence of a manganese chelator, lactate. The concept and the potential benefits this system holds will be discussed in further detail.
Keywords: Water -- Purification; Ultrafiltration; Enzymes; Membranes (Technology)